Narva kujutamine nõukogude aja teejuhis - Jelena Nõmm (Mäetagused)
The material analysed in the article consists of guidebooks on Narva published in the Soviet era: “Narva. Guidebook” (1960) by Evgeny Krivosheev; “Narva” (1960) by Silvi Kihu; “Narva. Guidebook” (1967) by Evgeny Krivosheev and Konstantin Mikhailov; “Narva. Guidebook” (1981) by Evgeny Krivosheev; “Narva. Guidebook” (1990) by Eldar Efendiev. The focus of attention is on the ideological functions of guidebooks. Under the influence of official ideology and historiography, the texts of Soviet guidebooks on Narva modelled the historical narrative about the city and created an image of Narva, which experienced a second birth after 1944. The image of Narva in the guidebooks splits into two images: historical (ancient, old) Narva and modern (Soviet, socialist, young, new) Narva. These two Narvas are dissimilar to each other: we cannot recognise the ancient city in the image of modern Narva. The history of the Soviet-era Narva guidebook can be seen as a history of attempts to resolve this contradiction or to escape from it. The ideological task of the Soviet guide to Narva was to justify the history of the city after 1940. The image of ancient Narva fades before the image of modern Narva. Actually, the guidebook becomes a guide to the achievements of socialist Narva. It can be said that the Soviet guidebooks on Narva are a vivid example of the ideological pressure of the epoch on the author of the text. However, the Soviet era was not always unified; the loosening of Soviet ideology in the 1980s affected Narva guidebooks as well.